Power Optimization of Spark Ignition Engine by Fuzzy Logic Ignition Controller Based on Knock Detection - Agus Sujono; Raden Soekrisno; Eka Firmansyah; Oyas Wahyunggoro (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
Spark ignition engines have many advantages, but to increase the power and efficiency, they have a problem to set the right ignition timing, at which the maximum power can be delivered. In reality, the optimum ignition time is immediately prior to, or close to, the moment of detonation (knock). On the other hand, the value of this optimum ignition timing is dependent primarily on the rotation of the crank shaft and the level of throttle openings. To provide the right  timing proficiency level, it is very difficult to overcome the mechanical control system as found in conventional engines. So, in this study, a new electro-mechanical method based on Fuzzy Logic Ignition Controller (FLIC) which follows the pattern of the timing in the detonation chart was created. The results of the FLIC study, in fact, are able to provide correction for each spark plug ignition, according to the data on the chart of the optimal ignition timings for all combinations of engine rotations and throttle openings. From the final data recorded, it can be said that the FLIC influence on the power output which increases of up to 15% above normal. DOI: http://dx.doi.org/10.11591/telkomnika.v14i2.7597